Understanding patient-reported outcome measures in colorectal cancer. (18th March 2019) - Besson, Alex; Deftereos, Irene; Chan, Steven; Faragher, Ian G; Kinsella, Rita; Yeung, Justin MC
Quality of life has become increasingly regarded as a key outcome measurement for cancer patients. Patient-reported outcome measures (PROMs) represent the tools used to ascertain self-reported quality of life. This review provides a summary of the literature regarding the use of PROMs in colorectal cancer and evaluates the advantages and limitations of generic and disease specific questionnaires that can be utilized in clinical practice. Factors that influence PROMs are outlined, including cancer characteristics, patient factors and treatment methods. Finally, future directions for the use of PROMs in colorectal cancer to inform healthcare delivery at an individual- and systems-based level are discussed.